Spain : list of leaflets & pamphlets (1937)
018b-0080-001 SPAIN. LIST OF LEAFLETS & PAMPHLETS. August 1936. LEAFLET: (N.C.L.) "The Spanish Workers' Defence of Democracy", appealing for contributions to the International Solidarity Fund. September 1936. PAMPHLET: (T.U.C.) "The Spanish Problem" - the speeches at Plymouth Congress. LEAFLET: (N.C.L.) "The Truth about Spain", another edition of the August leaflet. "The Drama of Spain, 1931-1936" by A. Ramos Oliveira. October 1936. PAMPHLET: (Lab. P.) "The Agony of Spain" - speeches of Señor de Asua and Señora de Palencia at Edinburgh Conference. November 1936. (reprinted) December 1936. Pamphlet: (N.C.L.) "Catholics and the Civil War in Spain". January 1937. LEAFLET: (N.C.L.) Statement on the Labour Relief Work for Spain. LEAFLET: (N.C.L.) Accompanied the Statement, appealing for contributions to International Solidarity Fund. PAMPHLET: (Lab. P.) "A Catholic looks at Spain". (reprinted) February 1937. PAMPHLET: (Lab. P.) "Madrid. The 'Military' Atrocities of the Rebels." March 1937. LEAFLET: (N.C.L.) "More Truth about Spain" - still another edition of August 1936 leaflet. May 1937. LEAFLET: (N.C.L.) May Day Manifesto. July 1937. LEAFLET: (N.C.L.) "Your Shillings will save Lives!" 292/946/18b/80